The development of latch-type locking mechanism - Abdul Halim, Hafizah (2006)
This thesis describes the development of a simple and low cost latch-type locking mechanism that can be applied to an automatic door. The system is an add-on gadget for the existing door lock. A microcontroller, PIC l 6F84A from Microchip Technology Inc. was used to control a stepper motor which was connected to a latchtype locking mechanism. When a button is pressed, it will feed a signal to the microcontroller, which will move the latch. There are two types of rotation options provided: Clockwise rotation and Counter clockwise rotation. The clockwise rotation will moves the latch to unlock the door lock where as the counter clockwise rotation will moves the latch to lock position.